Decomposing Software Verification into Off-the-Shelf Components: An Application to CEGAR - Beyer, Dirk; Haltermann, Jan; Lemberger, Thomas; Wehrheim, Heike (2022 IEEE/ACM 44th International Conference on Software Engineering (ICSE), 2022)
Techniques for software verification are typically realized as cohesive units of software with tightly coupled components. This makes it difficult to reuse components, and the potential for workload distribution is limited. Innovations in software verification might find their way into practice faster if provided in smaller, more specialized components. In this paper, we propose to strictly decompose software verification: the verification task is split into independent subtasks, implemented by only loosely coupled components communicating via clearly defined interfaces. We apply this decomposition concept to one of the most frequently employed techniques in software verification: counterexample-guided abstraction refinement (CEGAR). CEGAR is a technique to iteratively compute an abstract model of the system. We develop a decomposition of CEGAR into independent components with clearly defined interfaces that are based on existing, standardized exchange formats. Its realization component-based CEGAR (C-CEGAR) concerns the three core tasks of CEGAR: abstract-model exploration, feasibility check, and precision refinement. We experimentally show that - despite the necessity of exchanging complex data via interfaces - the efficiency thereby only reduces by a small constant factor while the precision in solving verification tasks even increases. We furthermore illustrate the advantages of C-CEGAR by experimenting with different implementations of components, thereby further increasing the overall effectiveness and testing that substitution of components works well.